Pendekatan Empati sebagai Solusi Brand saat Pandemi COVID-19 - Fitorio Leksono (Aliansi Desainer Produk Industri Indonesia (ADPII), 2020)
The massive spread of Covid-19 not only brought disaster for Indonesian Indonesian from health perspectives, but also in economy amid the implementation of physical and social distancing that forced many people to stay at home. The economy impact was so huge that forced many companies to cut down their workforce and even some of them choose to closed down the business. Tulisan as a brand that produce wearable artworks products also hampered by this economic crisis. This publication studies the effectiveness of empathy study in order to help business like Tulisan in order to survive the pandemic Covid-19. The outcome of this research will serve as the evidence on the significance of Empathy Study of Design Thinking method for business, especially during time of crises like Pandemic Covid-19.